TINGKAT BAHAYA EROSI PADA TIAP SATUAN LAHAN DI DAS KANAIKAN BAGIAN HULU, KABUPATEN PASAMAN BARAT - Muhammad Arif (STKIP Pesisir Selatan, 2016)
AbstractThe purpose of this study to analyze and describe data on rainfall, erosivitis rainfall, soil characteristics and the level of erosion hazard in the watershed upstream part of the increase in West Pasaman. This research is classified as descriptive and the method used is survey method with the sample area. Sampling in the retractable in purposive sampling with a selected sample of 10 units of land that is considered to represent the research area. The results showed research area rainfall 2824.4 mm / year, erosivitas rainfall 2367.5 mm / year, the condition of land characteristics on the dusty soil texture in the form of clay, sandy clay loam, sand argillaceous, solum soil depth between 10-70 cm , slope between flat to very steep (5-50%, the highest slope length of 45 meters and the lowest is 6 meters, in the form of crop management, rice, woodland, brown, oil palm and shrubs, conservation techniques in the area of research in the form of traditional terrace and strip plants with contour. the level of erosion hazard in the area of research there are three categories: level erosion hazard medium was contained in land units K1 V Kmb Qh H, hazard heavy erosion level was contained in land units V2 III Kmb Puku H, while the level of erosion was very heavy there at 8 land units that is land units F1 I And Qh Pr, F1 I Kmb Muw Sw, V1 II Kmb Pm Qh, Qh Kmb II Sw V1, V2 Kmb Muwl Pr III, IV Kmb Muwl H V3, V3 IV Kmb Muwm Pm, V3 IV Kmb Qvta Pr.Keywords: land units, watersheds, erosion hazards